Stage fright: Perceptions and experiences of pre-service teachers in performing arts-based education in an inclusive setting - Brankley, Lisa A (University of Ottawa (Canada), 2010)
Approaches such as arts-based education optimize the goals of inclusive education, an emergent educational philosophy in Canada. However there is tension between this research, current classroom practice, and education policies. This study explores the perceptions of three primary/junior pre-service teachers as they engaged in the implementation of inclusion of students with exceptionalities using an arts-based approach. Data were collected through in-depth interviews with the participants (following Seidman's [2006] method) at three points during their teacher education experiences. Central findings and cross-case analysis focused on their contextual histories, teacher education experiences, and culminating reflections. Childhood events and environments influenced pre-service attitudes, while past engagement in the arts facilitated their implementation of an arts-based approach particularly in the absence of guidance from teacher education courses and their associate teacher. Participants cited academic, social, and personal benefits of implementing inclusion through the arts for students with exceptionalities. Implications for practice are discussed.
Keywords: Education, Performing Arts.; Education, Teacher Training.